Investigation of the spontaneous ﬁssion properties of neutron-deﬁcient nobelium isotopes - A. V. Isaev; A. I. Svirikhin; A. V. Andreev; A. V. Yeremin; I. N. Izosimov; A. N. Kuznetsov; A. A. Kuznetsova; O. N. Malyshev; A. G. Popeko; Yu. A. Popov; E. A. Sokol; M. L. Chelnokov; et al. (Eurasian Journal of Physics and Functional Materials, 2021)
In the last years we carried out several experiments aimed to investigate properties of short-lived SF isotopes. The neutron-deﬁcient isotopes of nobelium were produced in fusion-evaporation reactions using206,208Pb targets and an intense48Ca-beam. Fusion-evaporation residues were separated by the SHELS separator and implanted into a large-area double-sided (48 × 48) strip silicon detector surrounded by3He-based neutron counters. Half-lives and decay branching ratios for252,254No isotopes were measured. The average number of neutrons per spontaneous ﬁssion of254No determined for the ﬁrst time.